Preparation and properties of amine functionalized graphene filled epoxy thin film nano composites for electrically conductive adhesive - Ghaleb, Z. A.; Mariatti, binti Mustapha; Zulkifli, bin Mohamad Ariff; Ervina, Junaidi (Springer New York LLC, 2018)
The study was carried out to investigate the effect of amine coupling agent of graphene nanopowder (GNP) on the properties of epoxy-based electrically conductive adhesives. Amine-based coupling agent for GNP (m-GNP)/epoxy thin film nanocomposites and GNP/epoxy thin film nanocomposites were fabricated using an ultrasonication and spin-coating techniques. Subsequently, the effect of GNP with different filler loading (0.05–1 vol%) on the tensile properties and electrical properties of the epoxy composites was studied. The GNPs functionalized with amine coupling agent was confirmed with FTIR, AFM and Raman spectroscopy. Generally, it was found that the addition of GNPs decreased the tensile properties of epoxy composites. However, m-GNP/epoxy composites showed higher tensile properties than GNP/epoxy composites at the same filler loading. While, it was found that the percolation threshold of the m-GNP/epoxy composites (0.6 vol%) was much higher than that of the GNP/epoxy (0.1 vol%). Morphological analysis of the GNP fillers by TEM images showed that the average dimensions of m-GNPs layers were far smaller than the average dimensions of GNPs before functionalization. SEM images of the tensile samples cross section confirmed the existence of strong interfacial bonding between m-GNP and the epoxy matrix. © 2017, Springer Science+Business Media, LLC, part of Springer Nature.